Hearing Teachers at the Primary Schools for the Hearing Impaired in the Czech Republic and the in Deaf Culture Knowledge - Kučera, Pavel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
When pupils with hearing impairment have hearing parents, the school for hearing impaired is usually the first institution where those students first encounter Czech sign language. That is why teachers should have information about Deaf culture, customs and history. Only then can a student with a hearing  impairment  become convinced that his language is full-fledged so he can be proud of it, as well as his Deaf culture. Teachers at Primary schools for the hearing impaired are supposed to be role models for pupils with hearing impairment and be one of the first people who are influencing them in this area. The aim of the research was to find out the level of Deaf cultural awareness of hearing teachers and whether they do know the customs and traditions of the Deaf. The research was conducted through the form of through structured interviews.